2007
DOI: 10.1016/j.nbd.2006.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The formation of peripheral myelin protein 22 aggregates is hindered by the enhancement of autophagy and expression of cytoplasmic chaperones

Abstract: The accumulation of misfolded proteins is associated with various neurodegenerative conditions. Peripheral myelin protein 22 (PMP22) is a hereditary neuropathy-linked, short-lived molecule that forms aggresomes when the proteasome is inhibited or the protein is mutated. We previously showed that the removal of pre-existing PMP22 aggregates is assisted by autophagy. Here we examined whether the accumulation of such aggregates could be suppressed by experimental induction of autophagy and/or chaperones. Enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 60 publications
4
101
0
Order By: Relevance
“…Although the signaling events that target misfolded PMP22 and SIMPLE into aggresomes have not been identified, our previous finding 17 of parkin-mediated K63 linked poly-ubiquitination in targeting misfolded protein to aggresomes via interactions with the dynein adaptor protein HDAC6 suggest that as yet-to-be identified E3 ligases and adaptor proteins could be responsible for targeting misfolded PMP22 and SIMPLE to aggresomes. Moreover, we 3 and others 18 showed that PMP22-and SIMPLE-positive aggresomes are tightly surrounded by autophagosome markers (Fig. 1 and step 9) and degraded by autophagy ( Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 60%
“…Although the signaling events that target misfolded PMP22 and SIMPLE into aggresomes have not been identified, our previous finding 17 of parkin-mediated K63 linked poly-ubiquitination in targeting misfolded protein to aggresomes via interactions with the dynein adaptor protein HDAC6 suggest that as yet-to-be identified E3 ligases and adaptor proteins could be responsible for targeting misfolded PMP22 and SIMPLE to aggresomes. Moreover, we 3 and others 18 showed that PMP22-and SIMPLE-positive aggresomes are tightly surrounded by autophagosome markers (Fig. 1 and step 9) and degraded by autophagy ( Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 60%
“…Autophagy, stimulated via fasting or rapamycin, or an increase in the heat shock response, can improve the phenotype of some PMP22-related neuropathies (Fortun et al, 2007;Rangaraju et al, 2008Rangaraju et al, , 2010Madorsky et al, 2009), and salubrinal enhancement of the integrated stress response (ISR) ameliorated hypomyelination and oligodendrocyte loss in cultured hippocampal slices exposed to IFN- (Lin et al, 2008).…”
Section: Pharmacological Targeting Of Eif2mentioning
confidence: 99%
“…The proteasome is a multi-catalytic complex involved in a variety of cellular processes, including the degradation of short-lived proteins (Goldberg, 2003). PMP-22 is a short-live molecule, that form aggregates when the proteasome is inhibited or the protein is mutated (Fortun et al, 2007). It is conceivable that the amount of PMP-22 targeted for degradation is increased in the gene duplication and point mutations disease, which could overwhelm the proteasome and lead to the accumulation of miss-folded proteins along the secretory pathway.…”
Section: Schwann Cell Express a Mutate Pmp22 Gen In Cmt-1a Animal Modmentioning
confidence: 99%